Long-term follow-up of hospitalized COVID-19 patients with interstitial lung involvement - Özdemir, Özer; Polat, Gülru; Gayaf, Mine; Güldaval, Filiz; Serçe Unat, Damla; Şimşek, Tarık (The Journal of Infection in Developing Countries, 2026)
Introduction: Data regarding the residual lung findings persisting beyond 12 months from acute infection in patients with COVID-19 with pulmonary involvement are scarce. This study investigates the long-term radiological and functional findings of previously hospitalized COVID-19 patients who had residual pulmonary involvement at 3–6-month follow-up. Methodology: This retrospective cohort study was an extended analysis of a previously published study, including patients with COVID-19 pneumonia hospitalized between June 2020 and March 2021. Residual lung involvement due to COVID-19 pneumonia was classified according to the presence of ground glass opacities, honeycombing, traction bronchiectasis, reticulations, and parenchymal bands. Results: 51 out of the 157 patients with abnormal chest findings in high-resolution computed tomography (HRCT) scans at 3–6-month follow-up were included. Mean age of the study population was 60.5 ± 10.5 years; 35 subjects were male (68.6%). HRCT controls were obtained 25.7 ± 6.36 months after the diagnosis. There was regression of predefined radiological involvement in 39 patients (76.5%), whereas 11 patients (21.6%) exhibited stable findings, and one patient had progressive lung involvement with a usual interstitial pneumonia pattern. Persistent residual parenchymal bands were found mostly in ICU-admitted patients (p = 0.04), and reticulations were seen in patients with a CT severity score > 18 (p = 0.04). Conclusions: In most patients with pulmonary sequelae, lesions showed improvement after 18 months, with complete resolution in about one third of patients after a 6-month follow-up. There was a correlation between initial severity and persistence of lung abnormalities.